High social strain and physical health: Examining the roles of anxious arousal, body mass index, and inflammation - Guevara, Jasmin E. (Psychoneuroendocrinology, 2019)
Social relationships have powerful effects on physical health. Indeed, high social strain (i.e., frequent negative interactions with friends, family, or one’s partner) increases risk of morbidity and mortality. Frequent social strain leads to anxious arousal and an increased body mass index (BMI), both of which may be underlying mechanisms for the association between social strain and health given that persistent anxious arousal promotes damaging biological and behavioral conditions contributing to increased inflammation. When chronic, heightened inflammation results in the deterioration of overall health. The purpose of the current study was to investigate anxious arousal, BMI, and inflammation as underlying mechanisms of the association between social strain and health. A sample of 763 middle aged adults participating in the Midlife in the United States (MIDUS 2) study completed self-report measures of social strain, anxious arousal, and physical health. Blood collection and a physical examination were completed to measure BMI and inflammation. Using 5,000 bootstrap samples, results indicated that greater social strain was associated with poorer self-reported health (SRH) due to the serial pathway from high anxious arousal to BMI and inflammation.